CALCULATION AND VISUALIZATION OF QUANTUM-MECHANICAL TUNNEL EFFECT - K.A. Kabylbekov,; A.D. Dasibekov,; Kh.K. Abdrakhmanova,; P.A. Saidakhmetov,; B.Sh. Kedelbaev, (Academic Scientific Journal of Computer Science, 2019)
The article presents calculations and visualization of wave packet tunneling through the potential barrier of various widths done by using the MATLAB software. The graph of distribution of the probability density along barrier width is obtained in two and three dimensions. The article contains materials about quantummechanical tunnel effect such as the reflection of the part of the wave packet from the potential barrier and passing through the barrier of the other part. Calculations and visualization of the tunneling process are performed for various widths of the barrier. Figures given in the article show the probability of finding the particle at a certain time, i.e. the square of the absolute value of the state vector 2  . The part of the total number of particles tunnels through barrier, the other part reflects from it. The probability of tunneling increases with decrease of the barrier width. The detailed analysis of the graphs reveals that the wave function exponentially decreases inside the potential barrier therefore the observation of this effect requires a rather small width of the barrier. Students are offered to develop programs for various widths of the potential barrier. Results of experiments are used during the study of the quantum mechanics.